2021
DOI: 10.3847/psj/ac2dff
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Iron and Nickel in the Coma of C/1996 B2 (Hyakutake): Production Rates, Emission Mechanisms, and Possible Parents

Abstract: Two papers recently reported the detection of gaseous nickel and iron in the comae of over 20 comets from observations collected over two decades, including interstellar comet 2I/Borisov. To evaluate the state of the laboratory data in support of these identifications, we reanalyzed archived spectra of comet C/1996 B2 (Hyakutake), one of the nearest and brightest comets of the past century, using a combined experimental and computational approach. We developed a new, many-level fluorescence model that indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…-Metal atoms such as Fe have been observed by the Rosetta/ROSINA instrument in the coma of comet 67P/C-G, confirming remote observations in a suite of other comets (Manfroid et al 2021;Bromley et al 2021). These observations were performed while the comet was active near its perihelion and we obtained Si/H 2 O ∼ 2 × 10 −5 , Na/H 2 O ∼ 3 × 10 −6 , and Fe/H 2 O ∼ 5 × 10 −8 with substantial uncertainties of up to a factor of ten, respectively.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…-Metal atoms such as Fe have been observed by the Rosetta/ROSINA instrument in the coma of comet 67P/C-G, confirming remote observations in a suite of other comets (Manfroid et al 2021;Bromley et al 2021). These observations were performed while the comet was active near its perihelion and we obtained Si/H 2 O ∼ 2 × 10 −5 , Na/H 2 O ∼ 3 × 10 −6 , and Fe/H 2 O ∼ 5 × 10 −8 with substantial uncertainties of up to a factor of ten, respectively.…”
Section: Discussionsupporting
confidence: 63%
“…Based on earlier identification of iron and nickel atoms in a suite of comets (Manfroid et al 2021;Bromley et al 2021) searched DFMS m/Q = 56 Da/e data for the presence of Fe. The spectra, one of row A and one of row B (cf.…”
Section: Iron (Fe)mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, Fulle et al (2007) analyzed also the HI-1 images and reported a production rate of Q Fe ∼ 10 30 s −1 for comet C/2006 P1 (McNaught) at heliocentric distance r H = 0.25 au. Bromley et al (2021) and Manfroid et al (2021) measured the production rates of iron to be Q Fe ∼ 10 21 -10 24 s −1 for a list of comets at heliocentric distances of ∼0.7-3 au. As for sodium, for instance, comet C/1995 O1 (Hale-Bopp) was measured to produce sodium atoms at a rate of ∼10 25 -10 26 s −1 at ∼1 au from the Sun (Cremonese et al 1997;Rauer et al 1998;Wilson et al 1998), and C/2012 S1 (ISON) had Q Na ∼ 10 23 -10 24 s −1 (Schmidt et al 2015).…”
mentioning
confidence: 99%
“…photon processing, solar/stellar wind, cosmic rays, magnetospheric and micrometeoroid bombardment. Furthermore, the detection of neutral atomic Fe and Ni in the coma of the comet C/1996 B2 (Hyakutake) 33 as well as on 20 other comets 34 raises the question not only of the associated formation mechanisms of the two TMs, but what chemistry can be developed once Fe and/or Ni remain bound to the rocky surface displaying free valences. Regarding the selected Ni ligand sphere (Fig.…”
mentioning
confidence: 99%